Penentuan Tingkat Kompetensi Soft Skill Mahasiswa Menggunakan Metode Analytical Hierarchy Process dan Promethee - Hardiansyah Putra; Sumijan (Jurnal Informasi dan Teknologi, 2020)
Bureau of Student Advisory Center (BSAC) Universitas Pembangunan Panca Budi is a center for career development and character building for students. In this case, a soft skill seminar is conducted to find the best candidate employees in the field of recruitment offered based on the criteria of student soft skill training. Determining the level of soft skill competences of students using the Analytical Hierarchy Process (AHP) method and the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE). For decision support systems using the AHP and PROMETHEE methods in determining the level of soft skill competencies, in order to obtain prospective employees who have the required soft skill competency level. Data collection was carried out by conducting research. The data is taken from the seminar results with 100 participants. The data that has been collected, processed and analyzed before being used as input and output as a basis for learning or training using the AHP and Promethee methods. Based on the calculations of the two methods, namely the AHP and Promethee methods, there are differences in calculations. In other words, because Promethee does not support the determination of weights and the hierarchy of criteria and does not have the assurance of consistency when determining weights like AHP. So that the program execution has a different time in the results, in the AHP method, program execution until the final result is obtained is better than the Promethee method. AHP has advantages in determining weights and criteria hierarchy, while Promethee has advantages in the alternative ranking process using different preference and weight functions.